1990
DOI: 10.1007/bf02252925
|View full text |Cite
|
Sign up to set email alerts
|

Brain protection of nicergoline against hypoxia: EEG brain mapping and psychometry

Abstract: In a double-blind, placebo-controlled trial human brain function and mental performance as well as the antihypoxidotic properties of nicergoline were studied utilizing blood gas analysis, EEG brain mapping and psychometry. Hypoxic hypoxidosis was experimentally induced by a fixed gas combination of 9.8% oxygen (O2) and 90.2% nitrogen (N2) equivalent to 6,000 m altitude, which was inhaled for 23 min under normobaric conditions by 16 healthy volunteers. They received randomized after an adaptation session placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…In contrast to our results, some previous studies showed that hypoxia caused an increase in delta activity (Burykh, 2005;Kraaier et al, 1988;Ozaki et al, 1995;Saletu et al, 1990;Schellart and Reits, 2001). The reason for this contradiction may be a few methodological differences among the studies.…”
Section: Eeg Wavescontrasting
confidence: 56%
See 4 more Smart Citations
“…In contrast to our results, some previous studies showed that hypoxia caused an increase in delta activity (Burykh, 2005;Kraaier et al, 1988;Ozaki et al, 1995;Saletu et al, 1990;Schellart and Reits, 2001). The reason for this contradiction may be a few methodological differences among the studies.…”
Section: Eeg Wavescontrasting
confidence: 56%
“…Second, Saletu et al (1990) showed that a permanent effect occurred in the central nervous system by hypoxia at the altitude of 6000 m (19.685 ft) and there was no permanent effect at lower altitudes. In our study, the hypoxia level approximately corresponds to 3400 m (11.154 ft).…”
Section: Eeg Wavesmentioning
confidence: 99%
See 3 more Smart Citations